UNLOCKING CLIMATE SOLUTIONS: CARBON CREDITS, OFFSETS, AND CLEAN DEVELOPMENT MECHANISM - PANKAJ KUMAR JAIN; PRAMA ESTHER SOLOMAN; CHHAGAN LAL; HITESH PAREEK (The Bioscan, 2024)
Carbon credits are instrumental in creating a market-based mechanism for incentivizing emission reductions and promoting sustainable practices. By trading carbon credits, businesses and industries can efficiently manage their carbon footprint by reducing emissions internally or purchasing credits from projects that mitigate emissions elsewhere. This flexibility allows cost-effective solutions to combat climate change while encouraging innovation and investment in clean technologies. Reducing greenhouse gas emissions is just one aspect of carbon offset projects. Such projects also support by creating jobs and educational prospects, technology transfer, and providing economic and social benefits worldwide. CDM serves as a vital mechanism for channeling climate finance, fostering international cooperation, and incentivizing emission reductions while promoting sustainable development worldwide.